Left Ventricular Assist Device Implantation with Concomitant Replacement of the Ascending Aorta - Bauer, Sebastian Johannes; Sugimura, Yukiharu; Immohr, Moritz Benjamin; Mehdiani, Arash; Lichtenberg, Artur; Akhyari, Payam (The Thoracic and Cardiovascular Surgeon Reports, 2024)
Dilated cardiomyopathy (DCM) is one of the main causes for end-stage heart failure. Until the transplantation, left ventricular assist devices (LVAD) have become an established treatment. We report a case of a 66-year-old patient with ischemic and DCM and suspected aortic ulcer formation. LVAD was implanted in the same session with a supracoronary aortic replacement. Bilateral cannulation of the subclavian arteries omitted the need of circulatory arrest and proximal aortic cross-clamping. Pneumonia-associated decarboxylation failure prolonged the postoperative intensive care period. The patient was finally discharged home on the 115th postoperative day.
Keywords: aortic disease; aorta/aortic; cardiopulmonary bypass; left ventricular assist device